Pendapat Tokoh Mui Kota Malang Terhadap Putusan Nomor 0637/Pdt.G/2010/ Pa Wsb Tentang Penyelesaian Hutang Bersama - Dian Ticha Pratiwi (Journal of Islamic Business Law, 2018)
The study aims to know the opinion of the characters of MUI in Malang City against the decision of the Number 0637/Pdt.G/2010/Pa Wsb to the completion of the debt together after a divorce from the Perundang-Undangan. What kind of this research is research the law of the empirical approach juridical sociological. The gathering data obtained through a live interview with the use of methods of analysis diskriptif. The study concluded, that the MUI in Malang City a different opinion against the decision of the Courts Wonosobo : First of all, according to the MUI the completion of the debt with what's going on for a married couple who've been divorced is not always ditunaikan the two sides to the burden of the same. Secondly, if the debt by the parties with a financial institution is obliged to perform is the party who signed loan agreements between the husband or wife. The three, but if debt comes from the deal doesn't have the debt is the responsibility of husband.